(untitled) (Research, Society and Development, 2020)
The work aims to present the benefits of the use of the Swiss ball by parturients to relieve pain in labor. Searches were carried out in the MEDLINE, LILACS and SCIELO databases. The inclusion criteria for the studies were: research that addressed the theme, published in Portuguese, English or Spanish, in the format of original articles, as well as randomized, controlled experimental studies, from November to December 2019. Obtained as result 47 articles initially identified by means of the researched databases, of these six publications were selected that met the inclusion criteria and answered the research question of this review. The studies analyzed showed that the Swiss ball induces a significant reduction in pain during labor. It is concluded that there are benefits for parturients when using the Swiss ball, reducing their levels of anxiety, discomfort and consequently facilitating the process for vaginal delivery.